Does acid-base equilibrium correlate with remnant liver volume during stepwise liver resection? - Golriz, Mohammad; Abbasi Dezfouli, Sepehr; Tinoush, Parham; Majlesara, Ali; Brenner, Thorsten; Mehrabi, Arianeb (American journal of physiology. Gastrointestinal and liver physiology, 2017)
Small for size and flow syndrome (SFSF) is one of the most challenging complications following extended hepatectomy (EH). After EH, hepatic artery flow decreases and portal vein flow increases per 100 g of remnant liver volume (RLV). This causes hypoxia followed by metabolic acidosis. A correlation between acidosis and posthepatectomy liver failure has been postulated but not studied systematically in a large animal model or clinical setting. In our study, we performed stepwise liver resections on nine pigs to defined SFSF limits as follows: step 1: segment II/III resection, step 2: segment IV resection, step 3: segment V/VIII resection (RLV: 75, 50, and 25%, respectively). Blood gas values were measured before and after each step using four catheters inserted into the carotid artery, internal jugular vein, hepatic artery, and portal vein. The pH, HCO3−, and base excess (BE) decreased, but HCO3− values increased after 75% resection in the portal and jugular veins. EH correlated with reduced BE in the hepatic artery. Pco2 values increased after 75% resection in the jugular vein. In contrast, arterial Po2 increased after every resection, whereas the venous Po2 decreased slightly. There were differences in venous HCO3−, BE in the hepatic artery, and Pco2 in the jugular vein after 75% liver resection. Because 75% resection is the limit for SFSF, these noninvasive blood evaluations may be used to predict SFSF. Further studies with long-term follow-up are required to validate this correlation.NEW & NOTEWORTHY This is the first study to evaluate acid-base parameters in major central and hepatic vessels during stepwise liver resection. The pH, HCO3−, and base excess (BE) decreased, but HCO3− values increased after 75% resection in the portal and jugular veins. Extended hepatectomy correlated with reduced BE in the hepatic artery. Because 75% resection is the limit for small for size and flow syndrome (SFSF), postresection blood gas evaluations may be used to predict SFSF.